Recurrent Peroneal Tendon Luxation: A Case Report and Review of the Literature - Belhan, Oktay; Karakurt, Lokman; Yılmaz, Erhan; Serin, Erhan; Bektaş, Bülent (Fırat University, 2005)
The peroneal tendons are located within a fibroosseous tunnel at the posterior aspect of the distal fibula. Peroneal tendon instability, which is rarely encountered, was first described in 1803 by Monteggia in a balet dancer. A twenty-year-old male patient referred to our clinic with pain at the lateral side of his right ankle during motion. History revealed that patient had ankle sprain 6 months before presenting to our clinic. After clinical examination and radiologic assessment, peroneal tendon instability was diagnosed and surgical treatment was performed. In the present study, we aimed to present the results of our surgical teratment as well as the functional outcomes of the surgery.©2005, Fırat Üniversitesi, Tıp Fakültesi

Peroneal tendonlar, fibulanın alt kısmının arkasında fibroosseöz bir tünel içerisinde yerleşmişlerdir. Peroneal tendon instabilitesi ilk defa 1803 yılında Monteggia tarafından bir bale dansçısında tanımlanmıştır ve nadir olarak görülmektedir. Yirmi yaşındaki erkek hasta, sağ ayak bileği dış yan kısmında hareket sırasında ağrı nedeni ile kliniğimize müracaat etti. Hastanın öyküsünde kliniğimize müracaat etmeden 6 ay önce ayak bileği burkulması vardı. Klinik muayene ve radyolojik değerlendirme sonrası hastaya peroneal tendon instabilitesi tanısı konup cerrahi tedavi yapıldı. Biz bu çalışmamızda, yaptığımız cerrahi tedaviyi ve elde ettiğimiz fonksiyonel sonucu sunmayı amaçladık. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Tekrarlayan Peroneal Tendon Çıkığı:Olgu Sunumu ve Literatürün Gözden Geçirilmesi